Elimination of plasmids pKM 101 and F'lac from Salmonella typhimurium and Escherichia coli by bisammonium salt. The effect of outer membrane pattern - Sýkora, P; Ceplíková, V; Foltýnová, Z; Horniak, L; Ebringer, L (Folia microbiologica, 1991)
Plasmid-curing activity of N,N'-bis(decyldimethyl)-1,6-hexanediammonium dibromide, BDHD, was tested on six different plasmids in E. coli and plasmid pKM 101 in S. typhimurium. BDHD eliminated the F'lac plasmid from E. coli cells only with a low efficiency. Plasmid pKM 101 was eliminated from S. typhimurium cells significantly and this effect was dependent on an outer membrane pattern. A deep-rough mutant of S. typhimurium is completely resistant to curing activity of BDHD, while part-rough and smooth cells are susceptible to it. In contrast to pKM 101, a cryptic plasmid being present in S. typhimurium cells was not eliminated by BDHD. The curing activity of sodium dodecyl sulfate, acridine orange, crystal violet, and promethazine was also affected by the outer membrane pattern of S. typhimurium cells.
Keywords: lipopolysacharidy; Salmonella typhimurium; Membrane Lipids; membránové lipidy; buněčná membrána; Quaternary Ammonium Compounds; Plasmids; kvartérní amoniové sloučeniny; Cell Membrane; Lipopolysaccharides; Escherichia coli; plazmidy